Music Streaming, Festivals, and the Eventization of Music. - Maasø, Arnt (Popular Music & Society, 2018)
A key aspect of music-streaming services is the user's access to their vast libraries and abundant choices anytime and anywhere. This article explores how artists performing at a large music festival in Norway were streamed before, during, and after the festival over the course of four different years. The data shows that festival streams grew by more than 40% compared to control weeks and were particularly pronounced among users who lived near the venue. The article then argues that changes in listening patterns may reflect a more general shift towards the "eventization" of streaming media.